FAKTOR-FAKTOR DAN UPAYA DALAM MENANGANI STRESS PADA DOKTER DI TENGAH PANDEMI COVID 19 - Syahidah, Sumayyah Nurul (Universitas Brawijaya, 2022)
The Covid-19 pandemic that occurred in various parts of the world greatly impacted the work of physicians and other health workers. Active cases that continue to rise have resulted in physicians who are directly involved in treating patients at risk of experiencing stress at work. The stress that physicians feel is caused by many internal and external factors. The aim of this systematic review is to identify the causative factors and what efforts can be made to manage stress on the physicians in the midst of a pandemic. Systematic database searches using Springer Link, Scopus, Google Scholar, ScienceDirect, and Mendeley. Keywords to look for relevant research include: